PERANAN ODITUR MILITER DALAM PEMBUKTIAN TINDAK PIDANA PERZINAHAN OLEH ANGGOTA MILITER TERHADAP KELUARGA BESAR TNI (KBT) - Ferry Youdiek Oktariawan Eka Jaya (Kerta Dyatmika, 2021)
ABSTRACT Military Attorney as public prosecutors within the TNI have the primary function of carrying out prosecutions in trials in Military Courts based on legal evidence by always observing religious, humanitarian and moral norms and having to explore the legal and justice values ​​that live in society and must pay attention to the interests of national defense and security. This study aims to find out how the role of Military Attorney as public prosecutors in military justice is in accordance with Law Number 31 of 1997 concerning Military Courts in conducting the verification process, as well as examining trials of adultery crimes committed by members of the military against the TNI Large Family in Military Courts III-14 Denpasar. This type of research used in discussing the problem of this study is to use empirical legal research. Empirical law research is research in the form of empirical studies to find theories about the process of occurrence and about the process of working of law in society. The results of the discussion are Military Attorney in proving adultery crime which is to present witnesses, defendants and examine evidence and Military Attorney are able to prove the elements in their claims, both in examining witnesses, defendants and evidence of adultery cases in the Military Court III-14 Denpasar conducted in private, but for reading indictments and claims made openly for Witnesses who were unable to present their statements can be read in accordance with the minutes of the examination.